Negative electrode material of low-temperature lithium ion battery and preparation method of low-temperature lithium ion battery
By using ion impregnation method, methane in situ cracking and acid etching methods in the negative electrode materials of lithium-ion batteries, a multi-porous structure negative electrode material was prepared, which solved the problem of traditional lithium-ion batteries being unable to charge and attenuate in low-temperature environments, and achieved excellent electrochemical performance under low-temperature conditions.
Patent Information
- Application Number
- CN202411803096.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Traditional lithium-ion batteries cannot be charged in a low temperature environment below 0°C, and the performance of lithium-ion batteries at low temperatures is sharply attenuated due to the low lithium-ion transmission rate, which poses a safety hazard.
A multi-porous structure negative electrode material prepared by ion impregnation method, methane in situ cracking and acid etching is used. This material stores lithium ions through the hollow structure of nanotubes, improving the conductivity and lithium ion diffusion rate.
The discharge platform voltage and discharge capacity of the negative electrode material are increased in a low temperature environment, solving the problems of performance attenuation and safety hazards of lithium-ion batteries, and realizing the function of supporting charging at temperatures of -20℃ and above.
Smart Images

Figure CN119673992A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a low-temperature lithium ion battery negative electrode material and a method for preparing the low-temperature lithium ion battery. Background Art
[0002] As a new energy product, lithium-ion batteries have been widely used in many fields such as drone products, digital products, security wearables, and power tools. However, traditional lithium-ion batteries cannot be charged under environmental conditions below 0°C. Because when traditional lithium-ion batteries are charged in a low-temperature environment below 0°C, lithium ions are very easy to precipitate on the surface of the negative electrode to form lithium dendrites. Long-term repeated charging in a low-temperature environment will seriously damage the material structure of the lithium-ion battery, causing the battery performance to decay sharply, and the battery will also have safety hazards due to lithium precipitation. The main reason for this situation is that the diffusion rate of lithium ions is small at lower temperatures, and the charge transfer impedance between the electrode and the electrolyte interface is large during the lithium insertion process. Since the performance of low-temperature lithium-ion batteries is mainly affected by the transmission rate of lithium ions in the negative electrode material, improving the diffusion rate of lithium ions in the graphite negative electrode is the key to improving the low-temperature performance of the battery. In order to solve this problem, it is planned to carry out a large number of experimental demonstrations on the modification research and formulation ratio of the negative electrode raw materials to develop a set of lithium-ion batteries that can support charging at temperatures of -20°C and above. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a low-temperature lithium-ion battery negative electrode material in view of the deficiencies of the above-mentioned prior art. The negative electrode material is prepared by ion impregnation, in-situ cracking of methane and acid etching, has a multi-aperture structure, and utilizes the hollow structure of nanotubes to effectively store lithium ions, thereby improving the conductivity of the negative electrode material, effectively increasing the diffusion rate of lithium ions in the negative electrode material, and improving the discharge platform voltage and discharge capacity of the negative electrode material in a low-temperature environment, thereby solving the problem that the negative electrode material affects the performance of lithium-ion batteries due to the low lithium ion transmission rate at low temperatures.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a low-temperature lithium-ion battery negative electrode material, characterized in that it includes a porous carbon material and a carbon nanomaterial coated on the porous carbon material, and the carbon nanomaterial is distributed in the pores and surface of the porous carbon material; the negative electrode material is prepared by a method comprising the following steps:
[0005] Step 1, preparing a precursor solution of Fe, Ni or Cu metal ions;
[0006] Step 2: adding the carbon material and the precipitant to the precursor solution prepared in step 1 for post-treatment to obtain a dried product;
[0007] Step 3, grinding the dried product obtained in step 2 and placing it in a muffle furnace for high-temperature activation to obtain an activated product;
[0008] Step 4: placing the activated product obtained in step 3 in a tubular reactor, introducing a methane mixed gas and heating the reactor to perform a methane cracking reaction;
[0009] Step 5: The activated product after the methane cracking reaction in step 4 is etched with hydrochloric acid, washed by centrifugation with deionized water, and dried to obtain a negative electrode material.
[0010] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that the precursor of the Fe metal ion in step 1 is at least one of FeCl3, Fe(NO3)3 and FeSO4, the precursor of the Cu metal ion is Cu(NO3)2, the precursor of the Ni metal ion is Ni(NO3)2.6H2O, and the concentration of Fe, Ni or Cu metal ions is 1.2mol / L to 1.6mol / L. By controlling the concentration of metal ions, it is avoided that too high a content of metal ions is accumulated on the surface of the carbon material after high-temperature activation, which is not conducive to the dispersion of metal ions on the surface and inside of the carbon material, and affects the uniformity of the pores generated in the carbon material by the subsequent methane cracking reaction.
[0011] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that the carbon material in step 2 is graphite powder, the precipitant is ammonium carbonate, and the amount of ammonium carbonate is 1.2 to 2.0 times the amount of Fe, Ni or Cu metal ions in the precursor solution, and the amount of carbon material is 0.75 to 1 times the amount of precursor salt in the precursor solution. By controlling the addition ratio of the precipitant, it is ensured that the active metal ions are completely precipitated.
[0012] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that the post-treatment in step 2 is: first stirring at 60° C. for 8 hours, filtering and drying the filter residue in an oven at 120° C. Stirring during post-treatment promotes the deposition of active metal ions on the surface of the carbon material.
[0013] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that the high-temperature activation process described in step three is: heating to 700°C at a rate of 5°C / min for calcination for 8h, and grinding to obtain an activated product. Usually, under a 95% Ar-5% O2 protective atmosphere, the temperature is first raised to 500°C at a rate of 10°C / min and maintained for 5min, and then heated to 700°C at a rate of 5°C / min. Different temperatures during the high-temperature activation process will form different crystal phases. The present invention strictly controls the high-temperature activation process, especially the temperature, so that the metal ions adsorbed and deposited on the surface of the carbon material react to form metal oxides, so that the metal oxides undergo partial oxidation-reduction reactions with methane to generate active metal elements, and further undergo cracking reactions with methane to generate carbon nanomaterials, thereby avoiding the generation of impurities.
[0014] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that the methane volume concentration in the methane mixed gas in step 4 is 5%, and the flow rate is 60 mL / min; the temperature of the methane cracking reaction is 800° C. Usually, the time for the methane cracking reaction after the methane mixed gas is introduced is 30 minutes; and a mass spectrometer is used to monitor the generated gas of the methane cracking reaction to confirm the component content of the generated gas, and then confirm the loading amount of the carbon nanomaterial.
[0015] The above-mentioned low-temperature lithium-ion battery negative electrode material is characterized in that in step five, hydrochloric acid with a mass concentration of 15% is used to etch and remove the metal oxide, and the drying is dried in a drying oven at 120° C. for 12 hours.
[0016] At the same time, the present invention also discloses a method for preparing a low-temperature lithium-ion battery using the negative electrode material as described above, characterized in that the method comprises the following steps:
[0017] Step 1: Prepare the positive electrode sheet by dry batching the lithium cobalt oxide material, PVDF and conductive agent according to the mass ratio of 95.8-96.6:1.6-2.0:1.8-2.2;
[0018] Step 2: Prepare the negative electrode sheet by dry batching the negative electrode material, SBR and CMC according to the mass ratio of 97.3-97.8:1.2-2.0:1.3-1.8;
[0019] Step 3: Isolate the positive electrode sheet produced in step 1 and the negative electrode sheet produced in step 2 with an isolation film, and add electrolyte to prepare a lithium-ion battery.
[0020] The above method is characterized in that no conductive agent needs to be added during the production of the negative electrode sheet in step 2.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The present invention first mixes the carbon material with metal ions, performs post-treatment and high-temperature activation to obtain an activated product of a mixture of carbon material and metal oxides. In the subsequent methane cracking reaction, after the metal oxide undergoes a partial redox reaction with methane, the metal oxide generates a metal element, which further undergoes a cracking reaction with methane, and is coated and deposited on the surface of the carbon material and inside the pores to generate carbon nanomaterials including carbon nanotubes and carbon nanofibers. At the same time, when the hydrogen generated during the reaction is released from the inside of the carbon material, a large number of micropores are generated inside the carbon material, thereby improving the pore size distribution of the carbon material and increasing the porosity of the carbon material, thereby obtaining a negative electrode material with a multi-aperture structure, and cooperating with the hollow structure of the carbon nanotubes to effectively store lithium ions, thereby improving the conductivity of the negative electrode material, effectively increasing the diffusion rate of lithium ions in the negative electrode material, and improving the discharge platform voltage and discharge capacity of the negative electrode material under low temperature conditions, thereby being suitable for low-temperature lithium-ion batteries.
[0023] 2. The present invention modifies the negative electrode material through an in-situ reaction of methane cracking, and the in-situ generated carbon nanomaterials are evenly distributed and tightly combined on the surface and inside of the carbon material, which effectively improves the dispersion of the carbon nanomaterials, is beneficial to improving the migration ability of electrons in the negative electrode material under high-rate discharge, reduces the polarization phenomenon during the charge and discharge process, and improves the charge and discharge capacity of the lithium-ion battery. Therefore, the negative electrode material prepared by the method of the present invention has excellent electrochemical reaction performance, and is better than the in-situ generation of carbon nanomaterials on the surface and inside of the negative electrode material by methane cracking. Therefore, there is no need to further add conductive agent materials in the subsequent preparation of negative electrode sheets, which simplifies the batching process and reduces the difficulty of batching.
[0024] 3. The present invention adopts hydrochloric acid etching, on the one hand, to remove the excess metal oxides in the activated product after the methane cracking reaction, and on the other hand, to perform acid etching on the metal element generated by the partial redox reaction of the metal oxide and methane, thereby forming staggered pores in the negative electrode material, effectively increasing the storage space of the electrolyte, thereby increasing the rate of lithium ion insertion and extraction between the negative electrode plate and the electrolyte interface, and reducing the polarization phenomenon during the low-temperature discharge process of the lithium ion battery, thereby achieving high rate and low-temperature discharge performance of the lithium ion battery.
[0025] 4. The present invention improves the porosity of carbon materials and realizes the filling of carbon nanomaterials by adjusting the process parameters of the methane cracking reaction, thereby improving the porosity and conductivity of the negative electrode material, greatly improving the low-temperature rate performance of lithium-ion batteries, and enabling lithium-ion batteries to achieve excellent charge and discharge performance in temperatures of -20°C and above, and can be stored and used under high temperature conditions.
[0026] 5. The negative electrode material preparation method of the present invention is simple and has high production efficiency. The methane cracking reaction in the preparation process effectively consumes greenhouse gas methane and produces clean energy hydrogen, which helps to reduce the greenhouse effect.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of in-situ cracking of methane onto the active metal surface in Example 1 of the present invention.
[0029] Figure 2 This is a test diagram of the electrochemical performance of lithium-ion batteries prepared in Examples 1 to 3 of the present invention and Comparative Example 1 at a temperature above -20°C.
[0030] Figure 3 The electrochemical performance test diagram of the lithium-ion batteries prepared in Example 2 of the present invention and Comparative Example 1 at -20°C after 500T of cycling. DETAILED DESCRIPTION
[0031] Figure 1 Schematic diagram of in-situ cracking of methane onto the active metal surface in Example 1 of the present invention, Figure 1 It can be seen that methane and metal elements on the surface and inside of the negative electrode material are decomposed to produce carbon nanotubes. The hollow structure of the nanotubes can be used as a warehouse for lithium ion transmission, which is beneficial to the transmission of lithium ions in the electrode, so that the negative electrode material has a higher lithium ion transmission rate, improves the conductivity of the negative electrode material, and reduces the low-temperature polarization phenomenon of lithium-ion batteries.
[0032] The low-temperature lithium-ion battery negative electrode material of the present invention is described in detail through Examples 1 to 3.
[0033] Example 1
[0034] The negative electrode material of the low-temperature lithium-ion battery of this embodiment includes a porous carbon material and a carbon nanomaterial coated on the porous carbon material, and the carbon nanomaterial is distributed in the pores and surface of the porous carbon material; the negative electrode material is prepared by a method comprising the following steps:
[0035] Step 1: Dissolve Ni(NO3)2.6H2O in deionized water at 60°C to obtain 60 mL of a precursor solution with a concentration of 1.2 mol / L;
[0036] Step 2: Add 16 g of graphite powder and 8.29 g of precipitant ammonium carbonate to the precursor solution prepared in step 1, adjust the pH to 8 with ammonia water, stir in a 60° C. water bath for 8 h, filter and dry the residue in an oven at 120° C. for 12 h to obtain a dried product;
[0037] Step 3: Grind the dried product obtained in step 2 and place it in a muffle furnace. Under an argon protective atmosphere, heat it to 500°C at a rate of 10°C / min and keep it for 5min, then heat it to 700°C at a rate of 5°C / min and calcine it for 8h to obtain an activated product by grinding.
[0038] Step 4: placing 16 g of the activated product obtained in step 3 in a tubular reactor, introducing a methane mixture with a methane volume concentration of 5% at a flow rate of 60 mL / min and heating to 800° C. to perform a methane cracking reaction, while using a mass spectrometer to monitor the generated gas of the methane cracking reaction to confirm the component content of the generated gas, and then confirm the loading amount of the carbon nanomaterial;
[0039] Step 5: The activated product after the methane cracking reaction in step 4 is etched with hydrochloric acid having a mass concentration of 15% to remove the metal oxide, and then centrifuged and washed with deionized water and dried in a drying oven at 120° C. for 12 hours to obtain a negative electrode material.
[0040] The precursor solution in this embodiment can also be replaced by a precursor solution containing Fe or Cu metal ions, and the precursor of the Fe metal ions is at least one of FeCl3, Fe(NO3)3 and FeSO4, and the precursor of the Cu metal ions is Cu(NO3)2.
[0041] Example 2
[0042] The difference between this embodiment and embodiment 1 is that in step 1, the concentration of the precursor solution is 1.4 mol / L, and the mass of the precipitant ammonium carbonate is 9.67 g.
[0043] The precursor solution in this embodiment can also be replaced by a precursor solution containing Fe or Cu metal ions, and the precursor of the Fe metal ions is at least one of FeCl3, Fe(NO3)3 and FeSO4, and the precursor of the Cu metal ions is Cu(NO3)2.
[0044] Example 3
[0045] The difference between this embodiment and embodiment 1 is that in step 1, the concentration of the precursor solution is 1.6 mol / L, and the mass of the precipitant ammonium carbonate is 11.05 g.
[0046] The precursor solution in this embodiment can also be replaced by a precursor solution containing Fe or Cu metal ions, and the precursor of the Fe metal ions is at least one of FeCl3, Fe(NO3)3 and FeSO4, and the precursor of the Cu metal ions is Cu(NO3)2.
[0047] The method for preparing the low-temperature lithium-ion battery of the present invention is described in detail through Example 4.
[0048] Example 4
[0049] This embodiment includes the following steps:
[0050] Step 1: Prepare the positive electrode sheet by dry mixing the lithium cobalt oxide material, PVDF and the conductive agent in a mass ratio of 95.8:2.0:2.2, wherein the conductive agent is carbon nano slurry with a solid content of 4.3%;
[0051] Step 2: The negative electrode material of Example 2, SBR, and CMC are mixed by dry method in a mass ratio of 97:1.2:1.8 to prepare a negative electrode sheet;
[0052] Step 3: Isolate the positive electrode plate produced in step 1 and the negative electrode plate produced in step 2 with a highly air-permeable and high-porosity coated diaphragm made of PE material, and add an electrolyte containing LiPF6, EC, EMC, DMC and anti-low-temperature additives to prepare a lithium-ion battery.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 4 is that in step 2, conventional negative electrode materials are used to prepare the negative electrode sheet, and the preparation method of the conventional negative electrode material comprises the following steps:
[0055] Step 1: Wash the wood chips with deionized water, dry them in a drying oven at 120°C for 2 hours, then soak them in a 2M sulfuric acid solution, heat them in a constant temperature water bath at 70°C for 2 hours to remove metal impurities, filter and wash them with deionized water until they are neutral, and dry them at 120°C for 2 hours to obtain a pre-treated product for use;
[0056] Step 2: Mix the pretreatment product in step 1 with 2M FeCl3 solution and stir for 12 hours. After vacuum filtration, dry it in a 120°C drying oven for 12 hours. Then place it in a tubular reactor filled with nitrogen and keep it at 800°C for 3 hours for carbonization. Then, immerse it in 1M sulfuric acid for 12 hours, wash it with deionized water until it is neutral, and obtain unmodified, i.e., conventional negative electrode material after drying.
[0057] The lithium ion batteries prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were subjected to charge and discharge tests using a Xinwei test device: the lithium ion batteries were first charged and discharged at room temperature using a 0.5 CI A Discharge to 3.0V, then place at -20℃ for 4h, charge and discharge the battery at 1C, and record the charge and discharge capacity. The results are as follows Figure 2 and Figure 3 shown.
[0058] Figure 2 The electrochemical performance test diagram of the lithium ion batteries prepared in Examples 1 to 3 of the present invention and Comparative Example 1 at a temperature above -20°C is shown in FIG. Figure 2It can be seen that, compared with the lithium-ion battery prepared using conventional negative electrode materials in Comparative Example 1, the lithium-ion batteries prepared in Examples 1 to 3 of the present invention have excellent charge and discharge performance, among which Example 2 is the best.
[0059] Figure 3 The electrochemical performance test diagram of the lithium ion batteries prepared in Example 2 and Comparative Example 1 of the present invention after 500T of cycling at -20°C is shown in FIG. Figure 3 It can be seen that the gram capacity of the lithium ion battery assembled from the negative electrode material of Example 2 is 115.79 mAh / g, which is significantly greater than the gram capacity of the lithium ion battery assembled from the conventional negative electrode material in Comparative Example 1, which is 96.76 mAh / g, indicating that the lithium ion battery assembled from the negative electrode material prepared by the present invention has an excellent cycle retention rate at a low temperature of -20°C.
[0060] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A low-temperature lithium-ion battery negative electrode material, characterized in that: The negative electrode material comprises a porous carbon material and a carbon nanomaterial coated on the porous carbon material, and the carbon nanomaterial is distributed in the pores and surface of the porous carbon material; the negative electrode material is prepared by a method comprising the following steps: Step 1, preparing a precursor solution of Fe, Ni or Cu metal ions; Step 2: adding the carbon material and the precipitant to the precursor solution prepared in step 1 for post-treatment to obtain a dried product; Step 3, grinding the dried product obtained in step 2 and placing it in a muffle furnace for high-temperature activation to obtain an activated product; Step 4: placing the activated product obtained in step 3 in a tubular reactor, introducing a methane mixed gas and heating the reactor to perform a methane cracking reaction; Step 5: The activated product after the methane cracking reaction in step 4 is etched with hydrochloric acid, washed by centrifugation with deionized water, and dried to obtain a negative electrode material.
2. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In step 1, the precursor of the Fe metal ion is at least one of FeCl3, Fe(NO3)3 and FeSO4, the precursor of the Cu metal ion is Cu(NO3)2, the precursor of the Ni metal ion is Ni(NO3)2·6H2O, and the concentration of Fe, Ni or Cu metal ions is 1.2 mol / L to 1.6 mol / L.
3. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In step 2, the carbon material is graphite powder, the precipitant is ammonium carbonate, and the amount of ammonium carbonate is 1.2 to 2.0 times the amount of Fe, Ni or Cu metal ions in the precursor solution, and the amount of carbon material is 0.75 to 1 times the amount of precursor salt in the precursor solution.
4. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: The post-treatment in step 2 is: first stirring at 60° C. for 8 h, filtering and drying the filter residue in an oven at 120° C.
5. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: The high temperature activation process in step three is: heating to 700° C. at a rate of 5° C. / min and calcining for 8 h, and then grinding to obtain an activated product.
6. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: The methane volume concentration in the methane mixed gas in step 4 is 5%, and the flow rate is 60 mL / min; the temperature of the methane cracking reaction is 800°C.
7. A low-temperature lithium-ion battery negative electrode material according to claim 1, characterized in that: In step five, 15% mass concentration hydrochloric acid is used to etch and remove the metal oxide, and the drying is carried out in a drying oven at 120° C. for 12 hours.
8. A method for preparing a low-temperature lithium-ion battery using the negative electrode material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Step 1: Prepare the positive electrode sheet by dry batching the lithium cobalt oxide material, PVDF and conductive agent according to the mass ratio of 95.8-96.6:1.6-2.0:1.8-2.2; Step 2: Prepare the negative electrode sheet by dry batching the negative electrode material, SBR and CMC according to the mass ratio of 97.3-97.8:1.2-2.0:1.3-1.8; Step 3: Isolate the positive electrode sheet produced in step 1 and the negative electrode sheet produced in step 2 with an isolation film, and add electrolyte to prepare a lithium-ion battery.
9. The method according to claim 8, characterized in that No conductive agent needs to be added during the production of the negative electrode sheet in step 2.
Citation Information
Patent Citations
Method for in situ growth of axial geometry carbon structures in electrodes
CN111403733A
Preparation method of coal-based porous carbon fiber negative electrode material of lithium / sodium ion battery
CN114267829A
Electrode catalyst for fuel cell and its manufacturing method
JP2007005284A